2010
DOI: 10.1097/qai.0b013e3181c7d47b
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Mother-to-Child Transmission of HIV-1 Using Highly Active Antiretroviral Therapy in Rural Yunnan, China

Abstract: The project demonstrated that HAART for all infected pregnant women is effective with a vertical transmission rate of approximately 1%. Thus, this project provides a model for China to scale up its efforts to prevent mother-to-child transmission of HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
1
10
0
2
Order By: Relevance
“…In developing countries, alternatives to breastfeeding may be problematic [4142] , due to cultural norms [4344] , unavailability of adequate nutritional substitutes, and poor water quality leading to high mortality from diarrheal diseases. A study in Yunnan Province of China, however, demonstrated that PMTCT could achieve a transmission rate of 0.01 [12] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In developing countries, alternatives to breastfeeding may be problematic [4142] , due to cultural norms [4344] , unavailability of adequate nutritional substitutes, and poor water quality leading to high mortality from diarrheal diseases. A study in Yunnan Province of China, however, demonstrated that PMTCT could achieve a transmission rate of 0.01 [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The HIV epidemic in China varies substantially with regions and the prevalence is particularly high in Yunnan, Xinjiang, and Guangxi provinces, which are home to a large proportion of ethnic minorities and have weaker economies compared to other Chinese provinces. In the absence of interventions, the transmission rate is 0.35, but PMTCT has been found to be able to reduce the transmission rate to as low as 0.01 in rural China [12] . Low transmission rates are dependent on screening of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A taxa de TMI do HIV de 7,7% determinada no presente estudo é muito elevada quando confrontada com a de outros estudos: na Espanha (1,42%) 25 , numa província rural da China (1%) 26 , pelo Estudo Colaborativo Europeu (1,72%) 24 e na África do Sul (4,9%) 27 . Ela também é elevada quando comparada com a de outros estudos em nosso país [6][7][8] , sendo seus determinantes muito bem caracterizados na análise caso a caso dos menores infectados: diagnóstico tardio da infecção materna, uso incorreto do teste rápido, não contra-indicação da amamentação ao seio, baixa adesão das gestantes à terapia antirretroviral e persistência da amamentação após o diagnóstico da doença materna.…”
Section: Variávelunclassified